Assessment of efficiency of investment portfolio management (Journal of Economic Research & Business Administration, 2020)
This article discusses the important issues in the selection and management of the investment portfolio,which are used. In order to achieve the established level of profitability and reduce the level of risk,the basic principles of well-known economists and investment rules are presented. Discusses the variousfactors used to evaluate the effectiveness of portfolio management of financial investments. It was notedthat profitability and risk are the main parameters for the evaluation of any investment, including the investmentportfolio. There is always a trade between risk and return. Therefore, the combination of assetsaffects the quality of the portfolio. The selective model of G. Markowitz, who is the founder of the portfolio,is also analyzed. The model is designed to assess the risk and return of the portfolio and calculatetheir correlation and covariance.Among the analyzed factors-the coefficient of the square, Sortino ratio,omega ratio, beta coefficient, coefficient alpha, coefficient of VaR and others. Advantages of applicationof any coefficient were defined. It was stressed that the results of the study needed to be informed aboutthe portfolio using each factor and considered in an integrated manner. In improving the efficiency of theinvestment portfolio, the importance of investing in index funds was noted. In addition to the providedcoefficients, it is necessary to pay attention to the investor’s own goals, as well as to other indicators of the funds‘ activities. Sovereign wealth funds in the world today use different approaches to risk assessmentand the formation of their investment portfolios-one distributes its funds in favor of the most riskyassets, others adhere to conservative strategies. The management of such funds should be based on acarefully considered investment strategy.The results of the research are used in the framework of the correctformation of the investment portfolio and management.